Liquid crystal aligning agent, liquid crystal alignment film, and liquid crystal display element using same
By using a specific diamine as a raw material polyamic acid and imidized product, an efficient liquid crystal alignment agent is formed, and the problems of poor orientation and defects in the existing liquid crystal alignment films during the process of large-scale, high-definition and low-cost substrates are solved, and the excellent electrical characteristics and stability of the liquid crystal representation element are achieved.
Patent Information
- Application Number
- CN202510039108.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2016-08-30
- Filing Date
- 2017-08-25
- Publication Date
- 2025-03-14
AI Technical Summary
The existing liquid crystal orientation films have poor orientation and defects in the process of large-scale, high-definition and low-cost substrates, resulting in expression defects and dust production.
The liquid crystal aligning agent containing a polyamic acid and/or its imidized product is used to form a polymer by reacting with tetracarboxylic dianhydride, thereby improving the coating and film forming properties of the liquid crystal aligning film.
The excellent electrical characteristics of the liquid crystal orientation film are realized, the problems of coloring and loss of transparency are avoided, and the reliability and stability of the liquid crystal display element are improved.
Smart Images

Figure CN119620472A_ABST
Abstract
Description
[0001] This application is a divisional application of a Chinese patent application with an application date of August 25, 2017, application number 201780066004.1, and invention name “LIQUID CRYSTAL ALIGNMENT AGENT, LIQUID CRYSTAL ALIGNMENT FILM, AND LIQUID CRYSTAL DISPLAY ELEMENT USING THE SAME”. Technical Field
[0002] The present invention relates to a liquid crystal aligning agent, a liquid crystal aligning film and a liquid crystal display element using the same. Background Art
[0003] Liquid crystal alignment film is a component of liquid crystal display elements widely used as display devices, which plays the role of orienting liquid crystals in a certain direction. At present, the main liquid crystal alignment film used in industry is formed by using a liquid crystal alignment agent composed of polyamic acid (also called polyamideacid) or a solution of polyimide as a polyimide precursor. Specifically, it is obtained by applying a liquid crystal alignment agent on a substrate, heating and firing, and then performing a liquid crystal alignment treatment.
[0004] In the past, the liquid crystal orientation treatment was mainly performed by surface treatment using brushing, but it is usually difficult to perform highly uniform orientation treatment by brushing, and sometimes poor orientation of the liquid crystal or defects in the liquid crystal orientation film may occur, resulting in display defects or dust generation. In recent years, due to the large-scale, high-definition, and low-cost substrates used in panels, there is a tendency for the area of the substrate to expand and the unevenness to increase. When forming an orientation film on such a substrate, there is still room for improvement in the brushing treatment.
[0005] On the other hand, as an orientation treatment method to replace the brushing method, an orientation treatment using photoreaction has been proposed. Specifically, the following method is known: a film of a polymer having a specific part that can react with light, such as polyvinyl cinnamate, is formed on the surface of a substrate, and a method of imparting liquid crystal orientation ability by irradiating polarized light or non-polarized light radiation (photo-orientation method). According to this method, uniform liquid crystal orientation can be achieved without generating static electricity or dust, and the viewing angle can also be improved by orientation segmentation (see Patent Documents 1 and 2).
[0006] In addition, in the case of liquid crystal units such as TN (Twisted Nematic) and STN (Super Twisted Nematic), the liquid crystal alignment film must have the function of tilting the liquid crystal molecules at a predetermined angle (pretilt angle) relative to the substrate surface. In order to show the pretilt angle, a liquid crystal alignment film obtained by using polyamic acid, polyimide, etc. containing alkyl side chains, steroid skeleton side chains, side chains with ring structures, etc. is known (Patent Documents 3, 4, 5). In the alignment process using light, the pretilt angle is usually given by irradiating the radiation whose incident direction is inclined relative to the normal direction of the substrate to the substrate surface (see Patent Document 1).
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Document 1: Japanese Patent Application Laid-Open No. 6-287453
[0010] Patent Document 2: Japanese Patent Application Laid-Open No. 9-297313
[0011] Patent Document 3: Japanese Patent Application Laid-Open No. 05-043687
[0012] Patent Document 4: Japanese Patent Application Laid-Open No. 04-281427
[0013] Patent Document 5: Japanese Patent Application Laid-Open No. 02-223916 Summary of the invention
[0014] Problem that the invention aims to solve
[0015] As mentioned above, in the past, most of the liquid crystal alignment films were formed by using a liquid crystal alignment agent composed of a polyamic acid or a solution of a polyimide as a polyimide precursor, but in recent years, due to the large-scale, high-definition, and low-cost substrates used in panels, the liquid crystal alignment agent has various problems and room for improvement. In order to solve one of the problems in this topic, a liquid crystal alignment agent is proposed, which includes polyamic acid and / or a polyimide obtained by imidizing the polyamic acid, wherein the polyamic acid is obtained by reacting a diamine shown in the following formula (DA-3) as a raw material with a tetracarboxylic dianhydride component.
[0016]
[0017] The liquid crystal display element having the liquid crystal alignment film obtained by the liquid crystal alignment agent has excellent characteristics in terms of electrical properties (release of accumulated charge, etc.). On the other hand, when the liquid crystal alignment agent is used, the obtained liquid crystal alignment film is colored dark brown and loses transparency, and it is found that it sometimes has an adverse effect on the liquid crystal alignment element having the liquid crystal alignment film.
[0018] The object of the present invention is to provide a liquid crystal aligning agent, which uses the above-mentioned diamine compound as a raw material of a polymer contained in the liquid crystal aligning agent, namely polyamic acid, thereby maintaining excellent properties, and the obtained liquid crystal aligning film will not be colored black-brown and lose transparency, etc., which will have an adverse effect on the liquid crystal aligning element.
[0019] Solutions for solving problems
[0020] The present inventors have conducted intensive studies to achieve the above-mentioned object and have completed the present invention as a result.
[0021] The present invention provides a liquid crystal aligning agent, characterized in that it contains at least one polymer selected from the group consisting of a polyamic acid and a polyimide obtained by imidizing the polyamic acid, wherein the polyamic acid is obtained by reacting a diamine component containing a diamine having a structure represented by the following formula [1] with a tetracarboxylic dianhydride component.
[0022]
[0023] (In the formula, A represents a thermally releasable group that is replaced by a hydrogen atom by heating at a temperature of 150 to 300°C. The hydrogen atom possessed by the benzene ring may be substituted by an alkyl group having 1 to 5 carbon atoms, an alkoxy group having 1 to 5 carbon atoms, or a halogen group. * represents a connecting bond.)
[0024] Effects of the Invention
[0025] The liquid crystal alignment agent of the present invention is characterized in that it contains a polyamic acid with a diamine represented by formula [1] (hereinafter also referred to as a specific diamine) as a raw material and / or a polyimide obtained by imidizing the polyamic acid, but the corresponding polymer has very high solubility in polar solvents such as N-methylpyrrolidone (NMP) and good handling properties during polymerization. The liquid crystal alignment agent containing the corresponding polymer has excellent coating and film-forming properties, and further, a liquid crystal alignment film can be obtained in which the decrease in voltage retention is suppressed even when exposed to light irradiation.
[0026] Furthermore, compared with the liquid crystal aligning agent comprising a polyamic acid or its polyimide which is made from the diamine compound (DA-3) described later having a structure similar to that of a specific amine, the liquid crystal aligning agent of the present invention has a transparency and is not colored dark brown, so that a liquid crystal aligning film can be formed which does not have an adverse effect on the liquid crystal display element.
[0027] As to why the liquid crystal alignment agent of the present invention can obtain the above-mentioned excellent effect, it can be roughly inferred as follows. That is, the diamine of the above formula (DA-3) having a similar structure to the diphenylamine skeleton of the same specific diamine has a secondary amino group in its structure that is more reactive than the primary amino group, and the secondary amino group reacts in the reaction process with the tetracarboxylic dianhydride component for obtaining polyamic acid, etc., causing an undesirable three-dimensional reaction. As a result, it can be considered that the obtained reactant is colored and the characteristics as a liquid crystal alignment agent are reduced.
[0028] The specific diamine of the present invention has a highly reactive secondary amino group in its structure similar to that of the above formula (DA-3), but the secondary amino group is protected by a thermally leaving group, and therefore does not cause an undesirable three-dimensional reaction during the reaction with the tetracarboxylic dianhydride component for obtaining the polyamic acid. As a result, it is believed that no coloring occurs and the properties as a liquid crystal aligning agent are not reduced.
[0029] Furthermore, in the liquid crystal alignment agent of the present invention, the polyamic acid and polyimide as the contained polymers have an amino group protected by a heat-leaving group, but as described later, the amino group protected by the heat-leaving group can be converted into an amino group deprotected by the heat-leaving group due to the heating during the firing process during the process of coating the liquid crystal alignment agent on a substrate and firing to form a liquid crystal alignment film.
[0030] The deprotected amino group regains its reactivity, and the amino group generated by the removal reacts in the molecule to form a heterocycle, etc., and generates a rigid side chain, which will act as a good inducing site for the pretilt angle. In addition, the amino group after the thermal leaving group is removed is not all used for the above cyclization reaction, but a part is also used for intermolecular reactions, which helps to improve the film strength and improve the reliability by cross-linking with low molecular components in the polymer.
[0031] Therefore, the polyamic acid and polyimide using the specific diamine of the present invention are unlikely to peel off during brushing treatment, and are unlikely to suffer a decrease in voltage holding ratio or an increase in ion density even when exposed to long-term high temperature, backlighting, and the like. DETAILED DESCRIPTION
[0032] <Specific diamine of the present invention>
[0033] The diamine used as a raw material of the liquid crystal aligning agent of this invention is a diamine which has a structure represented by following formula [1].
[0034]
[0035] In the above formula [1], A is a heat-leaving group that is replaced by hydrogen by heating at 150 to 300° C., which is the calcination temperature of the liquid crystal aligning agent of the present invention. The heat-leaving group is preferably able to leave at 170 to 300° C., particularly preferably 180 to 250° C. * represents a connecting bond.
[0036] As the thermally leaving group, there can be mentioned organic groups of carbamates represented by benzyloxycarbonyl, 9-fluorenylmethoxycarbonyl, allyloxycarbonyl, tert-butoxycarbonyl (also called Boc group), etc. From the viewpoint of good leaving efficiency, leaving at a relatively low temperature, and leaving as a harmless gas, Boc group or 9-fluorenylmethoxycarbonyl is particularly preferred.
[0037] The hydrogen atoms on the benzene ring in the formula [1] may be arbitrarily substituted with an alkyl group or alkoxy group having 1 to 5 carbon atoms, preferably 1 to 3 carbon atoms, or a halogen group such as chlorine, bromine or fluorine.
[0038] The amino group contained in the specific diamine is preferably a primary amino group, and may be a secondary amino group substituted with an alkyl group having a relatively small molecular weight, such as a methyl group, an ethyl group, a propyl group, or a butyl group.
[0039] Preferred specific examples of the specific diamine include the following, but are not limited thereto. In addition, Boc in the formula represents a tert-butoxycarbonyl group.
[0040]
[0041] <Tetracarboxylic dianhydride component>
[0042] In order to obtain the polyimide precursor of the present invention, it is preferred to use tetracarboxylic dianhydride (also referred to as specific tetracarboxylic dianhydride) represented by the following formula [7] as a part of the tetracarboxylic dianhydride component.
[0043]
[0044] In the formula [7], Z1 is a tetravalent organic group having 4 to 13 carbon atoms and having an aromatic cyclic hydrocarbon group. Specifically, it is preferably a group represented by any one of the following formulae [7a] to [7k].
[0045]
[0046] In formula [7], from the viewpoint of polymerization reactivity and ease of synthesis, a preferred group for Z1 is a group represented by formula [7a] or formula [7g]. Among them, formula [7a] is most preferred.
[0047] When tetracarboxylic dianhydride of the structure of formula [7a] is used, it is preferably 20% by mass or more, more preferably 30% by mass or more of the total tetracarboxylic dianhydride component. All tetracarboxylic dianhydride components used in the production of the polyimide precursor may be tetracarboxylic dianhydride of the structure of formula [7a].
[0048] In the present invention, aliphatic tetracarboxylic dianhydride other than the specific tetracarboxylic dianhydride or other tetracarboxylic acid components can be used.
[0049] Examples of aliphatic tetracarboxylic dianhydrides include 1,2,3,4-butanetetracarboxylic dianhydride. Examples of alicyclic tetracarboxylic dianhydrides include 1,2,3,4-cyclobutanetetracarboxylic dianhydride, 1,2,3,4-tetramethyl-1,2,3,4-cyclobutanetetracarboxylic dianhydride, 1,2-dimethyl-1,2,3,4-cyclobutanetetracarboxylic dianhydride, 1,3-dimethyl-1,2,3,4-cyclobutanetetracarboxylic dianhydride, 1,3-diphenyl-1,2,3,4-cyclobutanetetracarboxylic dianhydride, 1,2,3 ,4-cyclopentanetetracarboxylic dianhydride, 1,2,4,5-cyclohexanetetracarboxylic dianhydride, 1,2,3,4-cycloheptanetetracarboxylic dianhydride, 2,3,4,5-tetrahydrofurantetracarboxylic dianhydride, 3,4-dicarboxy-1-cyclohexylsuccinic dianhydride, 2,3,5-tricarboxycyclopentylacetic dianhydride, 3,4-dicarboxy-1,2,3,4-tetrahydro-1-naphthalenesuccinic dianhydride, bicyclo[3,3,0]octane-2,4,6,8 -tetracarboxylic dianhydride, bicyclo[4,3,0]nonane-2,4,7,9-tetracarboxylic dianhydride, bicyclo[4,4,0]decane-2,4,7,9-tetracarboxylic dianhydride, bicyclo[4,4,0]decane-2,4,8,10-tetracarboxylic dianhydride, tricyclo[6.3.0.0<2,6>]undecane-3,5,9,11-tetracarboxylic dianhydride, 4-(2,5-dioxotetrahydrofuran-3-yl)-1,2,3 ,4-tetrahydronaphthalene-1,2-dicarboxylic dianhydride, bicyclo[2,2,2]oct-7-ene-2,3,5,6-tetracarboxylic dianhydride, 5-(2,5-dioxotetrahydrofuran)-3-methyl-3-cyclohexane-1,2-dicarboxylic dianhydride, tetracyclo[6,2,1,1,0,2,7]dodecanede-4,5,9,10-tetracarboxylic dianhydride, 3,5,6-tricarboxynorbornane-2:3,5:6 dicarboxylic dianhydride, etc.
[0050] Examples of other tetracarboxylic acid components include tetracarboxylic acid, tetracarboxylic acid dihalide, tetracarboxylic dianhydride, esters obtained by dialkyl esterifying the carboxylic acid group of tetracarboxylic acid, and esters obtained by dialkyl esterifying the carboxylic acid group of tetracarboxylic acid dihalide.
[0051] In consideration of the liquid crystal orientation, voltage holding characteristics, stored charge and other characteristics of the liquid crystal aligning film to be formed, one or more of the above-mentioned other tetracarboxylic acid components can be used.
[0052] <Polymer of the present invention>
[0053] The polymer of the present invention refers to a polyamic acid and / or a polyimide obtained by imidizing the polyamic acid.
[0054] <Polyamic acid>
[0055] The polyamic acid of the present invention is obtained by reaction of a diamine component containing a specific diamine and a tetracarboxylic dianhydride component.
[0056] In the diamine component for reacting with the above-mentioned tetracarboxylic dianhydride component to obtain polyamic acid, there is no restriction on the content ratio of specific diamine. The content of specific diamine in diamine component can be 100%. However, from the viewpoint of satisfying various characteristics required by liquid crystal alignment film, such as increasing the characteristics of pretilt angle of liquid crystal, improving the vertical orientation of liquid crystal, etc., various diamines can be used simultaneously. Therefore, the content ratio of specific diamine in diamine component used in polymerization is preferably 1 to 50 mol%, particularly preferably 5 to 30 mol%.
[0057] Among the diamine components, examples of diamines other than the specific diamine (hereinafter also referred to as other diamines) used simultaneously when the specific diamine is less than 100 mol% include alicyclic diamines, aromatic-aliphatic diamines, heterocyclic diamines, and aliphatic diamines.
[0058] As an example of an alicyclic diamine, 1, 4- diaminocyclohexane, 1, 3- diaminocyclohexane, 4, 4'- diaminodicyclohexylmethane, 4, 4'- diamino-3, 3'- dimethyldicyclohexylamine, isophoronediamine, etc. are mentioned.
[0059] Examples of the aromatic diamines include o-phenylenediamine, m-phenylenediamine, p-phenylenediamine, 2,4-diaminotoluene, 2,5-diaminotoluene, 3,5-diaminotoluene, 1,4-diamino-2-methoxybenzene, 2,5-diamino-p-xylene, 1,3-diamino-4-chlorobenzene, 3,5-diaminobenzoic acid, 1,4-diamino-2,5-dichlorobenzene, 4,4'-diamino-1,2-diphenylethane, 4,4'-diamino-2,2'-dimethylbibenzyl, 4,4'-diaminodiphenylmethane, 3,3'-diaminodiphenylmethane, 3,4'-diaminodiphenylmethane, 4,4'-diamino-3,3'-dimethyldiphenylmethane, 2,2'-diaminostilbene, 4,4'- diaminostilbene, 4,4'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, 4,4'-diaminodiphenyl sulfide, 4,4'-diaminodiphenyl sulfone, 3,3'-diaminodiphenyl sulfone, 4,4'-diaminobenzophenone, 1,3-bis(3-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)benzene, 1,4-bis(4-aminophenoxy)benzene, 3,5-bis(4-aminophenoxy)benzoic acid, 4,4'-bis(4-aminophenoxy)bibenzyl, 2,2-bis[(4-aminophenoxy)methyl]propane, 2,2-bis[4-(4-aminophenoxy)phenyl]hexafluoropropane, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, bis[4-(3-aminophenoxy)phenyl] 1,1-bis(4-aminophenyl)cyclohexane, α,α'-bis(4-aminophenyl)-1,4-diisopropylbenzene, 9,9-bis(4-aminophenyl)fluorene, 2,2-bis(3-aminophenyl)hexafluoropropane, 2,2-bis(4-aminophenyl)hexafluoropropane, 4,4'-diaminodiphenylamine, 2,4-diaminodiphenylamine, 1,8-diaminonaphthalene, 1,5-diaminonaphthalene, 1,5-diaminoanthraquinone, 1,3-diaminopyrene, 1,6-diaminopyrene, 1,8-diaminopyrene, 2,7-diaminofluorene, 1,3-bis(4-aminophenyl)tetramethyldisiloxane, benzidine, 2,2'-dimethylbenzidine, 1, 2-bis(4-aminophenyl)ethane, 1,3-bis(4-aminophenyl)propane, 1,4-bis(4-aminophenyl)butane, 1,5-bis(4-aminophenyl)pentane, 1,6-bis(4-aminophenyl)hexane, 1,7-bis(4-aminophenyl)heptane, 1,8-bis(4-aminophenyl)octane, 1,9-bis(4-aminophenyl)nonane, 1,10-bis(4-aminophenyl)decane, 1,3-bis(4-aminophenoxy)propane, 1,4-bis(4-aminophenoxy)butane, 1,5-bis(4-aminophenoxy)pentane, 1,6-bis(4-aminophenoxy)hexane, 1,7-bis(4-aminophenyl)heptane, 1,8-bis(4-aminophenyl)octane, 1,9-bis(4-aminophenyl)nonane, 1,10-bis(4-aminophenyl)decane, 1,3-bis(4-aminophenoxy)propane, 1,4-bis(4-aminophenoxy)butane, 1,5-bis(4-aminophenoxy)pentane, 1,6-bis(4-aminophenoxy)hexane, 1,7-bis(4-aminophenoxy)heptane, 1,8-bis(4-aminophenoxy)octane, 1,9-bis(4-aminophenoxy)nonane, 1,10-bis(4-aminophenoxy)decane, bis(4-aminophenyl) 1,3-malonate, bis(4-aminophenyl) 1,4-succinate, bis(4-aminophenyl) 1,5-glutarate, bis(4-aminophenyl) 1,6-adipate, bis(4-aminophenyl) 1,7-pimelate, bis(4-aminophenyl) 1,8-suberate, bis(4-aminophenyl) 1,9-azelate, bis(4-aminophenyl) 1,10-sebacate, 1,3-bis[4- 1,4-bis[4-(4-aminophenoxy)phenoxy]propane, 1,4-bis[4-(4-aminophenoxy)phenoxy]butane, 1,5-bis[4-(4-aminophenoxy)phenoxy]pentane, 1,6-bis[4-(4-aminophenoxy)phenoxy]hexane, 1,7-bis[4-(4-aminophenoxy)phenoxy]heptane, 1,8-bis[4-(4-aminophenoxy)phenoxy]octane, 1,9-bis[4-(4-aminophenoxy)phenoxy]nonane, 1,10-bis[4-(4-aminophenoxy)phenoxy]decane, etc.
[0060] Examples of the aromatic-aliphatic diamines include 3-aminobenzylamine, 4-aminobenzylamine, 3-amino-N-methylbenzylamine, 4-amino-N-methylbenzylamine, 3-aminophenethylamine, 4-aminophenethylamine, 3-amino-N-methylphenethylamine, 4-amino-N-methylphenethylamine, 3-(3-aminopropyl)aniline, 4-(3-aminopropyl)aniline, 3-(3-methylaminopropyl)aniline, 4-(3-methylaminopropyl)aniline, 3-(3- ... -(4-aminobutyl)aniline, 4-(4-aminobutyl)aniline, 3-(4-methylaminobutyl)aniline, 4-(4-methylaminobutyl)aniline, 3-(5-aminopentyl)aniline, 4-(5-aminopentyl)aniline, 3-(5-methylaminopentyl)aniline, 4-(5-methylaminopentyl)aniline, 2-(6-aminonaphthyl)methylamine, 3-(6-aminonaphthyl)methylamine, 2-(6-aminonaphthyl)ethylamine, 3-(6-aminonaphthyl)ethylamine, and the like.
[0061] Examples of the heterocyclic diamine include 2,6-diaminopyridine, 2,4-diaminopyridine, 2,4-diamino-1,3,5-triazine, 2,7-diaminodibenzofuran, 3,6-diaminocarbazole, 2,4-diamino-6-isopropyl-1,3,5-triazine, and 2,5-bis(4-aminophenyl)-1,3,4-oxadiazole.
[0062] Examples of the aliphatic diamine include 1,2-diaminoethane, 1,3-diaminopropane, 1,4-diaminobutane, 1,5-diaminopentane, 1,6-diaminohexane, 1,7-diaminoheptane, 1,8-diaminooctane, 1,9-diaminononane, 1,10-diaminodecane, 1,3-diamino-2,2-dimethylpropane, 1,6-diamino-2,5-dimethylhexane, 1,7-diamino-2,5-dimethylheptane, 1,7-diamino-4,4-dimethylheptane, 1,7-diamino-3-methylheptane, 1,9-diamino-5-methylheptane, 1,12-diaminododecane, 1,18-diaminooctadecane, and 1,2-bis(3-aminopropoxy)ethane.
[0063] A diamine compound having an alkyl group, a fluorinated alkyl group, an aromatic ring, an aliphatic ring, a heterocyclic ring, or a macrocyclic substitution product composed of these in a side chain may be used simultaneously. Specifically, diamines represented by the following formulas [DA1] to [DA26] are exemplified.
[0064]
[0065] (R6 is an alkyl group having 1 to 22 carbon atoms or a fluorinated alkyl group.)
[0066]
[0067] (S5 represents -COO-, -OCO-, -CONH-, -NHCO-, -CH2-, -O-, -CO- or -NH-, and R6 represents an alkyl group or a fluorinated alkyl group having 1 to 22 carbon atoms.)
[0068]
[0069] (S6 represents -O-, -OCH2-, -CH2O-, -COOCH2- or -CH2OCO-, and R7 represents an alkyl group, an alkoxy group, a fluorinated alkyl group or a fluorinated alkoxy group having 1 to 22 carbon atoms.)
[0070]
[0071] (S7 represents -COO-, -OCO-, -CONH-, -NHCO-, -COOCH2-, -CH2OCO-, -CH2O-, -OCH2- or -CH2-, and R8 represents an alkyl group, an alkoxy group, a fluorinated alkyl group or a fluorinated alkoxy group having 1 to 22 carbon atoms.)
[0072]
[0073] (S8 represents -COO-, -OCO-, -CONH-, -NHCO-, -COOCH2-, -CH2OCO-, -CH2O-, -OCH2-, -CH2-, -O- or -NH-, and R9 represents fluoro, cyano, trifluoromethyl, nitro, azo, formyl, acetyl, acetoxy or hydroxyl.)
[0074]
[0075] (R 10 is an alkyl group having 3 to 12 carbon atoms, and the cis-trans isomerism of 1,4-cyclohexylene is trans.
[0076]
[0077]
[0078] When the alignment treatment is performed by light, it is preferred to use a specific diamine and the diamines of [DA-1] to [DA-26] at the same time because a more stable pretilt angle can be obtained. As more preferred diamines that can be used at the same time, diamines of formulas [DA-10] to [DA-26] are preferred, and diamines of formulas [DA-10] to [DA-16] are more preferred. The preferred content of these diamines is not particularly limited, but is preferably 5 to 50 mol% in the diamine component, and is preferably 5 to 30 mol% from the viewpoint of printability.
[0079] Furthermore, the following diamines may also be used simultaneously.
[0080]
[0081] (m is an integer of 0 to 3, and in formula [DA-34], n is an integer of 1 to 5).
[0082] By containing diamines of formula [DA-27], formula [DA-28], etc., the voltage holding characteristics when formed into a liquid crystal alignment film can be improved, and diamines of formula [DA-29] to [DA-34] have the effect of reducing accumulated charge.
[0083] Furthermore, as other diamines, diaminosiloxane etc. represented by following formula [DA-35] are mentioned.
[0084]
[0085] (m is an integer from 1 to 10.)
[0086] Other diamines may be used alone or in combination of two or more in accordance with the liquid crystal orientation, voltage retention characteristics, stored charge and other characteristics when used as a liquid crystal aligning film.
[0087] <Preparation of polyamic acid>
[0088] For the method of obtaining the polyamic acid of the present invention by the reaction of a tetracarboxylic dianhydride component and a diamine component, a known method can be adopted. It is usually a method in which the tetracarboxylic dianhydride component and the diamine component are reacted in an organic solvent. The reaction of the tetracarboxylic dianhydride component and the diamine is relatively easy to carry out in an organic solvent and is advantageous in that no by-products are generated.
[0089] The organic solvent used for the reaction between the tetracarboxylic dianhydride component and the diamine is not limited as long as it is a solvent that can dissolve the generated polyamic acid. Specific examples thereof are given below.
[0090] Examples thereof include N,N-dimethylformamide, N,N-dimethylacetamide, N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, N-methylcaprolactam, dimethyl sulfoxide, tetramethylurea, pyridine, dimethyl sulfone, hexmethyl sulfoxide, γ-butyrolactone, isopropyl alcohol, methoxymethylpentyl alcohol, dipentene, ethyl amyl ketone, methyl nonyl ketone, methyl ethyl ketone, methyl isoamyl ketone, methyl isopropyl ketone, methyl cellosolve, ethyl cellosolve, methyl cellosolve acetate, and ethyl cellosolve. Acetate, Butyl Carbitol, Ethyl Carbitol, Ethylene Glycol, Ethylene Glycol Monoacetate, Ethylene Glycol Monoisopropyl Ether, Ethylene Glycol Monobutyl Ether, Propylene Glycol, Propylene Glycol Monoacetate, Propylene Glycol Monomethyl Ether, Propylene Glycol Tert-Butyl Ether, Dipropylene Glycol Monomethyl Ether, Diethylene Glycol, Diethylene Glycol Monoacetate, Diethylene Glycol Dimethyl Ether, Dipropylene Glycol Monoacetate Monomethyl Ether, Dipropylene Glycol Monomethyl Ether, Dipropylene Glycol Monoethyl Ether, Dipropylene Glycol Monoacetate Monoethyl Ether, Dipropylene Glycol Monopropyl Ether, Dipropylene alcohol monoacetate monopropyl ether, 3-methyl-3-methoxybutyl acetate, tripropylene glycol methyl ether, 3-methyl-3-methoxybutanol, diisopropyl ether, ethyl isobutyl ether, diisobutylene, amyl acetate, butyl butyrate, butyl ether, diisobutyl ketone, methylcyclohexene, propyl ether, dihexyl ether, dioxane, n-hexane, n-heptane, n-octane, diethyl ether, cyclohexanone, ethylene carbonate, propylene carbonate, methyl lactate, ethyl lactate, methyl acetate, ethyl acetate, n-butyl acetate, propyl acetate Glycol ester monoethyl ether, methyl pyruvate, ethyl pyruvate, 3-methoxy methyl propionate, 3-ethoxy methyl ethyl propionate, 3-methoxy ethyl propionate, 3-ethoxy propionic acid, 3-methoxy propionic acid, 3-methoxy propyl propionate, 3-methoxy butyl propionate, diethylene glycol dimethyl ether, 4-hydroxy-4-methyl-2-pentanone, 3-methoxy-N, N-dimethyl propionamide, 3-ethoxy-N, N-dimethyl propionamide, 3-butoxy-N, N-dimethyl propionamide etc. These can be used alone, and can also be used in combination. And, even if the solvent that can not dissolve polyamic acid, in the scope that the polyamic acid generated does not precipitate, can also be mixed in the above-mentioned solvent and use.
[0091] Furthermore, water in the organic solvent inhibits the polymerization reaction and further causes hydrolysis of the generated polyamic acid. Therefore, the organic solvent is preferably dehydrated and dried as much as possible.
[0092] When the tetracarboxylic dianhydride component and the diamine component are reacted in an organic solvent, the following methods can be cited: a method of stirring a solution obtained by dispersing or dissolving the diamine component in an organic solvent, and then directly adding the tetracarboxylic dianhydride component or adding it after dispersing or dissolving it in an organic solvent; a method of adding the diamine component to a solution obtained by dispersing or dissolving the tetracarboxylic dianhydride component in an organic solvent; a method of alternately adding the tetracarboxylic dianhydride component and the diamine component, and any of these methods can be used. In addition, when the tetracarboxylic dianhydride component or the diamine component is composed of a plurality of compounds, the reaction can be carried out in a pre-mixed state, or they can be reacted in sequence, or the low molecular weight bodies obtained by the separate reactions can be mixed and reacted to form a high molecular weight body.
[0093] The temperature at which the tetracarboxylic dianhydride component and the diamine component react can be selected from any temperature in the range of -20 to 150°C, preferably in the range of -5 to 100°C. In addition, although the reaction can be carried out at any concentration, it is difficult to obtain a high molecular weight polymer when the concentration is too low, and it is difficult to stir the reaction solution uniformly because the viscosity becomes too high when the concentration is too high. Therefore, the total concentration of the tetracarboxylic dianhydride component and the diamine component in the reaction solution is preferably 1 to 50% by mass, more preferably 5 to 30% by mass. The reaction can be carried out at a high concentration in the early stage, and then an organic solvent can be added.
[0094] In the polymerization reaction of polyamic acid, the total molar ratio of tetracarboxylic dianhydride components to diamine components is preferably 0.8 to 1.2, more preferably 0.9 to 1.1. As in a normal polycondensation reaction, the closer this molar ratio is to 1.0, the greater the molecular weight of the generated polyamic acid.
[0095] <Preparation of polyimide>
[0096] The polyimide of the present invention is a polyimide obtained by dehydrating and ring-closing the polyamic acid described above, and is useful as a polymer for obtaining a liquid crystal aligning film.
[0097] In the polyimide of the present invention, the dehydration ring-closure ratio (imidization ratio) of the amic acid group does not necessarily need to be 100%, and can be arbitrarily adjusted according to the application or purpose.
[0098] Examples of a method for imidizing a polyamic acid include a thermal imidization method in which a solution of a polyamic acid is directly heated, and a catalytic imidization method in which a catalyst is added to a solution of a polyamic acid.
[0099] The temperature when the polyamic acid is thermally imidized in a solution is 100 to 400° C., preferably 120 to 250° C., and the imidization is preferably performed while discharging water generated by the imidization reaction to the outside of the system.
[0100] The catalytic imidization of polyamic acid can be carried out by adding a basic catalyst and anhydride to a solution of polyamic acid, and stirring at -20 to 250°C, preferably 0 to 180°C. The amount of the basic catalyst is 0.5 to 30 times the mole of the amic acid group, preferably 2 to 20 times, and the amount of the anhydride is 1 to 50 times the mole of the amic acid group, preferably 3 to 30 times. As a basic catalyst, pyridine, triethylamine, trimethylamine, tributylamine, trioctylamine, etc. can be mentioned, among which pyridine has a moderate alkalinity for the reaction to proceed, so it is preferred. As anhydrides, acetic anhydride, trimellitic anhydride, pyromellitic anhydride, etc. can be mentioned, among which, when acetic anhydride is used, it is easy to purify after the reaction is completed, so it is preferred. The imidization rate using catalytic imidization can be controlled by adjusting the amount of catalyst, reaction temperature, reaction time, etc.
[0101] The molecular weight of the polymer contained in the liquid crystal aligning agent of the present invention is preferably 5,000 to 1,000,000, more preferably 10,000 to 150,000 as a weight average molecular weight measured by GPC (Gel Permeation Chromatography) method in consideration of the strength of the obtained coating film, workability during coating film formation, and uniformity of the coating film.
[0102] <Liquid Crystal Alignment Agent>
[0103] The liquid crystal aligning agent of the present invention is a coating liquid for forming a liquid crystal aligning film, and is a solution in which a resin component for forming a resin coating is dissolved in an organic solvent. The resin component comprises at least one polymer selected from the polymer of the present invention. The content of the resin component in the liquid crystal aligning agent is preferably 1 to 20% by mass, more preferably 3 to 15% by mass, and particularly preferably 3 to 10% by mass.
[0104] The resin component may be composed entirely of the polymer of the present invention, or may be mixed with other polymers. In this case, the content of the other polymer in the resin component is 0.5 to 15% by mass, preferably 1 to 10% by mass.
[0105] As this other polymer, polyamic acid or polyimide etc. which are obtained using the diamine compound other than a specific diamine compound as a diamine component which reacts with a tetracarboxylic dianhydride component are mentioned, for example.
[0106] The organic solvent used for the liquid crystal aligning agent of the present invention is not particularly limited as long as it is an organic solvent that can dissolve the resin component. Specific examples thereof are given below.
[0107] Examples thereof include N,N-dimethylformamide, N,N-dimethylacetamide, N-methyl-2-pyrrolidone, N-methylcaprolactam, 2-pyrrolidone, N-ethylpyrrolidone, N-vinylpyrrolidone, dimethyl sulfoxide, tetramethylurea, pyridine, dimethyl sulfone, hexamethyl sulfoxide, γ-butyrolactone, 3-methoxy-N,N-dimethylpropionamide, 3-ethoxy-N,N-dimethylpropionamide, 3-butoxy-N,N-dimethylpropionamide, 1,3-dimethyl-imidazolidinone, ethyl amyl ketone, methyl nonyl ketone, methyl ethyl ketone, methyl isoamyl ketone, methyl isopropyl ketone, cyclohexanone, ethylene carbonate, propylene carbonate, diethylene glycol dimethyl ether, 4-hydroxy-4-methyl-2-pentanone, etc. These may be used alone or in combination.
[0108] The liquid crystal aligning agent of the present invention may contain components other than those described above, and examples thereof include solvent substances that improve uniformity of film thickness or surface smoothness when the liquid crystal aligning agent is applied, and compounds that improve adhesion between a liquid crystal aligning film and a substrate.
[0109] Specific examples of the solvent (poor solvent) for improving uniformity of film thickness or surface smoothness include the following.
[0110] For example, isopropyl alcohol, methoxymethylpentyl alcohol, methyl cellosolve, ethyl cellosolve, butyl cellosolve, methyl cellosolve acetate, ethyl cellosolve acetate, butyl carbitol, ethyl carbitol, ethyl carbitol acetate, ethylene glycol, ethylene glycol monoacetate, ethylene glycol monoisopropyl ether, ethylene glycol monobutyl ether, propylene glycol, propylene glycol monoacetate, propylene glycol monomethyl ether, propylene glycol tert-butyl ether, dipropylene glycol monomethyl ether, diethylene glycol, diethylene glycol monoacetate, diethylene glycol Dimethyl ether, dipropylene glycol monoacetate monomethyl ether, dipropylene glycol monomethyl ether, dipropylene glycol monoethyl ether, dipropylene glycol monoacetate monoethyl ether, dipropylene glycol monopropyl ether, dipropylene glycol monoacetate monopropyl ether, dipropylene glycol dimethyl ether, 3-methyl-3-methoxybutyl acetate, tripropylene glycol methyl ether, 3-methyl-3-methoxybutanol, diisopropyl ether, ethyl isobutyl ether, diisobutylene, amyl acetate, butyl butyrate, butyl ether, diisobutyl ketone, methylcyclohexene, propyl ether , dihexyl ether, 1-hexanol, n-hexane, n-pentane, n-octane, diethyl ether, methyl lactate, ethyl lactate, methyl acetate, ethyl acetate, n-butyl acetate, propylene glycol acetate monoethyl ether, methyl pyruvate, ethyl pyruvate, methyl 3-methoxypropionate, methyl ethyl 3-ethoxypropionate, ethyl 3-methoxypropionate, 3-ethoxypropionic acid, 3-methoxypropionic acid, propyl 3-methoxypropionate, butyl 3-methoxypropionate, 1-methoxy-2-propanol, 1-ethoxy-2 -propanol, 1-butoxy-2-propanol, 2-butoxy-1-propanol, 2,6-dimethyl-4-heptanol, 1-phenoxy-2-propanol, propylene glycol monoacetate, propylene glycol diacetate, propylene glycol-1-monomethyl ether-2-acetate, propylene glycol-1-monoethyl ether-2-acetate, dipropylene glycol, 2-(2-ethoxypropoxy)propanol, methyl lactate, ethyl lactate, n-propyl lactate, n-butyl lactate, isoamyl lactate and the like solvents having low surface tension.
[0111] These poor solvents may be used alone or in combination of two or more. When the above solvent is used, it is preferably 5 to 80% by mass, more preferably 20 to 60% by mass of the whole solvent contained in the liquid crystal aligning agent.
[0112] Examples of the compound that improves uniformity of film thickness or surface smoothness include fluorine-based surfactants, silicone-based surfactants, and nonionic surfactants.
[0113] More specifically, examples include EFT EF301, EF303, and EF352 (Lighting Products Co., Ltd. ), F171, F173, R-30 (made by Dainippon Ink Chemical Co., Ltd.), F171, F173, R-30 (made by Dainippon Ink Chemical Co., Ltd.), F171 C430, FC431 (manufactured by Sumitomo 3M Co., Ltd.), アサヒガードAG710, サーフロンS-382 , SC101, SC102, SC103, SC104, SC105, SC106 (manufactured by Asahi Glass Co., Ltd. (Asahi Glass Co., Ltd.)), etc. The using ratio of these surfactants is preferably 0.01 to 2 parts by mass, more preferably 0.01 to 1 part by mass, with respect to 100 parts by mass of the resin component contained in the liquid crystal aligning agent.
[0114] As a specific example of the compound which improves the adhesiveness of a liquid crystal aligning film and a substrate, the functional silane-containing compound and the epoxy group-containing compound shown below are mentioned.
[0115] For example, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 2-aminopropyltrimethoxysilane, 2-aminopropyltriethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, 3-ureidopropyltrimethoxysilane, 3-ureidopropyltriethoxysilane, N-ethoxycarbonyl-3-aminopropyltrimethoxysilane, N-ethoxycarbonyl-3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, N-triethoxysilylpropyltriethylenetriamine, N-trimethoxysilylpropyltriethylenetriamine, 10-trimethoxysilyl-1,4,7-triazadecane, 10-triethoxysilyl-1,4,7-triazadecane, 9-trimethoxysilyl-3,6-diazanonyl acetate, 9-triethoxysilyl-3,6-diazanonyl acetate, N-benzyl-3-amino Propyl trimethoxysilane, N-benzyl-3-aminopropyl triethoxysilane, N-phenyl-3-aminopropyl trimethoxysilane, N-phenyl-3-aminopropyl triethoxysilane, N-bis(oxyethylene)-3-aminopropyl trimethoxysilane, N-bis(oxyethylene)-3-aminopropyl triethoxysilane, ethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, tripropylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, neopentyl glycol diglycidyl ether, 1,6-hexanediol diglycidyl ether, glycerol diglycidyl ether, 2,2-dibromoneopentyl glycol diglycidyl ether, 1,3,5,6-tetraglycidyl-2,4-hexanediol, N,N,N',N',-tetraglycidyl-m-xylylenediamine, 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, N,N,N',N',-tetraglycidyl-4,4'-diaminodiphenylmethane, etc.
[0116] In addition to improving the adhesion between the substrate and the film, it is preferred to further contain a phenolic plastic additive as follows in order to prevent a decrease in electrical characteristics due to backlight. Specific phenolic plastic additives are shown below.
[0117]
[0118] When using a compound that improves adhesion to the substrate, the amount used is preferably 0.1 to 30 parts by mass, more preferably 1 to 20 parts by mass relative to 100 parts by mass of the resin component. If the amount used is less than 0.1 parts by mass, the effect of improving adhesion cannot be expected, and if it is more than 30 parts by mass, the orientation of the liquid crystal sometimes deteriorates.
[0119] In addition to the above, within the scope that does not impair the effects of the present invention, the liquid crystal alignment agent of the present invention may also contain dielectrics and conductive substances to change the electrical properties of the liquid crystal alignment film, such as the dielectric constant and conductivity, and may also contain cross-linking compounds to increase the film hardness or density when the liquid crystal alignment film is made.
[0120] <Liquid crystal alignment film and liquid crystal display element>
[0121] The liquid crystal orientation agent of the present invention is coated on a substrate and fired, and then oriented by brushing or illumination, or can be used as a liquid crystal orientation film without orientation in vertical orientation applications. At this time, the substrate used is not particularly limited as long as it is a substrate with high transparency, and plastic substrates such as glass substrates, acrylic substrates, polycarbonate substrates, etc. can be used. In addition, from the viewpoint of process simplification, it is preferred to use a substrate formed with an ITO electrode for liquid crystal drive, etc. In addition, in a reflective liquid crystal display element, if it is only a single-sided substrate, an opaque substance such as a silicon wafer can also be used, and the electrode at this time can also use a material that reflects light such as aluminum.
[0122] The coating method of the liquid crystal aligning agent is not particularly limited, and is generally performed industrially by screen printing, offset printing, flexographic printing, inkjet printing, etc. Other coating methods include dip coating, roll coating, slit coating, spin coating, etc., and these methods can be used according to the purpose.
[0123] The liquid crystal alignment agent is applied to the substrate and then fired at 50 to 300°C, preferably 80 to 250°C, by a heating means such as a hot plate to evaporate the solvent, thereby forming a coating. If the thickness of the coating formed after firing is too thick, it is disadvantageous in terms of the power consumption of the liquid crystal display element. If it is too thin, the reliability of the liquid crystal display element is sometimes reduced, so it is preferably 5 to 300 nm, more preferably 10 to 100 nm. When the liquid crystal is horizontally oriented or tilted, the fired coating is treated by brushing or irradiating polarized ultraviolet rays.
[0124] The liquid crystal display element of the present invention is a liquid crystal display element produced by obtaining a substrate with a liquid crystal alignment film from the liquid crystal aligning agent of the present invention by the above-mentioned method, and then preparing a liquid crystal cell by a known method.
[0125] If an example of preparing a liquid crystal unit is given, the following method can be illustrated: a pair of substrates with liquid crystal alignment films formed thereon are prepared, spacers are spread on the liquid crystal alignment film of one substrate, the other substrate is bonded with the liquid crystal alignment film surface facing the inside, and liquid crystal is injected under reduced pressure and sealed; or liquid crystal is dripped on the surface of the liquid crystal alignment film with spacers spread thereon, and then the substrates are bonded and sealed, etc. The thickness of the spacer is preferably 1 to 30 μm, more preferably 2 to 10 μm.
[0126] Example
[0127] In order to explain the present invention in more detail, examples are given below, but the interpretation of the present invention is not limited to these examples. The abbreviations used in the examples and the methods of evaluating properties are as follows.
[0128]
[0129] <Organic Solvents>
[0130] NMP: N-methyl-2-pyrrolidone BCS: Butyl cellosolve
[0131] <Additives>
[0132] LS-4668: 3-Glycidoxypropyltriethoxysilane
[0133] <Viscosity measurement>
[0134] The viscosity of the solution was measured using an E-type viscometer TVE-22H (manufactured by Toki Sangyo Co., Ltd.) at a temperature of 25° C. with a sample amount of 1.1 mL and a conical rotor TE-1 (1°34′, R24).
[0135] <Production of Liquid Crystal Display Element>
[0136] First, prepare a substrate with electrodes. The substrate is a rectangular glass substrate with a length of 30 mm and a width of 35 mm and a thickness of 0.7 mm. On the substrate, as the first layer, an ITO electrode having a solid pattern for constituting a counter electrode is formed. On the counter electrode of the first layer, as the second layer, a silicon nitride (SiN) film formed by a CVD method is formed. The film thickness of the SiN film of the second layer is 500 nm, and it functions as an interlayer insulating film. On the SiN film of the second layer, as the third layer, a comb-shaped pixel electrode formed by patterning the IZO film is arranged to form two pixels, the first pixel and the second pixel. The size of each pixel is 10 mm in length and about 5 mm in width. At this time, the counter electrode of the first layer and the pixel electrode of the third layer are electrically insulated due to the action of the SiN film of the second layer.
[0137] The pixel electrode of the third layer has a comb-like shape formed by arranging a plurality of "く"-shaped electrode elements with a bent central portion. The width of each electrode element in the width direction is 3μm, and the interval between the electrode elements is 6μm. The pixel electrode forming each pixel is composed of an arrangement of a plurality of "く"-shaped electrode elements with a bent central portion, so the shape of each pixel is not a rectangle, but a shape similar to a bold "く" character that is bent in the central portion like the electrode elements. In addition, each pixel is divided into upper and lower parts with the central bent portion as the boundary, and has a first area on the upper side of the bent portion and a second area on the lower side.
[0138] When comparing the first area and the second area of each pixel, the electrode elements constituting the pixel electrodes are formed in different directions. That is, when the brushing direction of the liquid crystal alignment film described later is used as a reference, in the first area of the pixel, the electrode elements of the pixel electrode are formed at an angle of +10° (clockwise), and in the second area of the pixel, the electrode elements of the pixel electrode are formed at an angle of -10° (clockwise). Thus, the first area and the second area of each pixel are constructed as follows: the directions of the rotation action (plane switching) of the liquid crystal in the substrate surface induced by applying a voltage between the pixel electrode and the counter electrode are opposite to each other.
[0139] Next, the liquid crystal alignment agent is filtered with a filter with a pore size of 1.0 μm, and then spin-coated on the prepared substrate with electrodes and a glass substrate with an ITO film formed on the back of the substrate and a columnar spacer with a height of 4 μm. Then, after drying on a hot plate at 80°C for 2 minutes, it is calcined at 230°C for 20 minutes to obtain a polyimide film with a film thickness of 60 nm on each substrate. The polyimide film is brushed with a rayon cloth in a specific brushing direction (roller diameter 120 mm, rotation speed 500 rpm, moving speed 30 mm / second, and pressure 0.3 mm), and then irradiated with ultrasonic waves in pure water for 1 minute and dried at 80°C for 10 minutes to form a liquid crystal alignment film.
[0140] The obtained two substrates with liquid crystal alignment films were combined in a manner that their respective brushing directions were inversely parallel, leaving a liquid crystal injection port and sealing the surroundings to produce an empty cell with a cell gap of 3.5 μm. After vacuum injection of liquid crystal (MLC-3019, manufactured by MERCK Co., Ltd.) into the empty cell at room temperature, the injection port was sealed to obtain an antiparallel oriented liquid crystal cell. The obtained liquid crystal cell constituted an FFS mode liquid crystal display element. Subsequently, the obtained liquid crystal cell was heated at 120°C for 1 hour, left overnight, and then used for each evaluation.
[0141] <Evaluation of Liquid Crystal Orientation>
[0142] Using the liquid crystal unit produced as described above, apply an AC voltage of 10VPP at a frequency of 30Hz for 168 hours in a constant temperature environment of 60°C. Next, a short circuit state is formed between the pixel electrode and the counter electrode of the liquid crystal unit, and the unit is left at room temperature for one day in this state. After placement, the liquid crystal unit is set between two polarizing plates arranged in a manner such that the polarization axes are orthogonal, the backlight is pre-lit in a state where no voltage is applied, and the configuration angle of the liquid crystal unit is adjusted to minimize the brightness of the transmitted light. Then, the rotation angle when the liquid crystal unit is rotated from the angle at which the second area of the first pixel becomes darkest to the angle at which the first area becomes darkest is calculated as the angle Δ. For the second pixel, the second area is also compared with the first area to calculate the same angle Δ. Then, the average value of the angle Δ values of the first pixel and the second pixel is calculated as the angle Δ of the liquid crystal unit.
[0143] The smaller the angle Δ of the liquid crystal cell is, the higher the liquid crystal orientation is.
[0144] <Gardner Chroma>
[0145] The obtained liquid crystal aligning agent was left at room temperature for 24 hours, and then the Gardner chromaticity was measured. The Gardner chromaticity indicating the color tone was measured based on Japanese Industrial Standard JIS K 0071-2. The smaller the Gardner chromaticity, the lighter the color of the obtained liquid crystal aligning agent.
[0146] (Synthesis example 1)
[0147] A 50 mL four-necked flask equipped with a stirrer was placed in a nitrogen atmosphere, 0.773 g (2.58 mmol) of DA-1 and 2.54 g (10.4 mmol) of DA-4 were weighed, 46.5 g of NMP was added, and the mixture was dissolved by stirring while nitrogen was supplied. 2.71 g (12.4 mmol) of CA-2 was added while stirring the diamine solution, and the mixture was stirred at room temperature for 2 hours and then at 50° C. for 24 hours to obtain a polyamic acid solution (PAA-1, viscosity: 510.7 mPa·s).
[0148] (Synthesis example 2)
[0149] A 50 mL four-necked flask equipped with a stirrer was placed in a nitrogen atmosphere, 1.55 g (5.18 mmol) of DA-1 and 1.90 g (7.78 mmol) of DA-4 were weighed, 54.6 g of NMP was added, and the mixture was dissolved by stirring while nitrogen was supplied. 2.71 g (12.4 mmol) of CA-2 was added while stirring the diamine solution, and the mixture was stirred at room temperature for 2 hours and then at 50° C. for 24 hours to obtain a polyamic acid solution (PAA-2, viscosity: 505.4 mPa·s).
[0150] (Synthesis example 3)
[0151] A 50 mL four-necked flask equipped with a stirrer was placed in a nitrogen atmosphere, DA-1 0.773 g (2.58 mmol), DA-4 2.22 g (9.09 mmol) and DA-6 0.724 g (1.30 mmol) were weighed, and NMP 46.5 g was added and dissolved while stirring while nitrogen was supplied. CA-2 2.71 g (12.4 mmol) was added while stirring the diamine solution, and the mixture was stirred at room temperature for 2 hours and then at 50° C. for 24 hours to obtain a polyamic acid solution (PAA-3, viscosity: 505.4 mPa·s).
[0152] (Synthesis Example 4)
[0153] A 50 mL four-necked flask equipped with a stirrer was placed in a nitrogen atmosphere, 0.773 g (2.58 mmol) of DA-1 and 2.98 g (10.4 mmol) of DA-5 were weighed, 47.4 g of NMP was added, and the mixture was dissolved by stirring while nitrogen was supplied. 2.71 g (12.4 mmol) of CA-2 was added while stirring the diamine solution, and the mixture was stirred at room temperature for 2 hours and then at 50° C. for 24 hours to obtain a polyamic acid solution (PAA-4, viscosity: 525.3 mPa·s).
[0154] (Synthesis Example 5)
[0155] A 50 mL four-necked flask equipped with a stirrer was placed in a nitrogen atmosphere, 1.56 g (5.21 mmol) of DA-1 and 2.23 g (7.79 mmol) of DA-5 were weighed, 47.7 g of NMP was added, and the mixture was dissolved by stirring while nitrogen was supplied. 2.71 g (12.4 mmol) of CA-2 was added while stirring the diamine solution, and the mixture was stirred at room temperature for 2 hours and then at 50° C. for 24 hours to obtain a polyamic acid solution (PAA-5, viscosity: 510.4 mPa·s).
[0156] (Synthesis Example 6)
[0157] A 50 mL four-necked flask equipped with a stirrer was placed in a nitrogen atmosphere, DA-1 0.778 g (2.60 mmol), DA-5 2.60 g (9.08 mmol) and DA-6 0.724 g (1.30 mmol) were weighed, and 50.0 g of NMP was added, and stirred while nitrogen was supplied to dissolve. CA-2 2.71 g (12.4 mmol) was added while stirring the diamine solution, and the mixture was stirred at room temperature for 2 hours and then at 50° C. for 24 hours to obtain a polyamic acid solution (PAA-6, viscosity: 498.1 mPa·s).
[0158] (Comparative Synthesis Example 1)
[0159] A 50 mL four-necked flask equipped with a stirrer was placed in a nitrogen atmosphere, 2.79 g (14.0 mmol) of DA-3 was weighed, 47.1 g of NMP was added, and dissolved by stirring while nitrogen was supplied. 2.44 g (12.4 mmol) of CA-1 was added while stirring the diamine solution, and the mixture was stirred at 15° C. for 2 hours to obtain a polyamic acid solution (PAA-7, viscosity: 121.1 mPa·s).
[0160] (Comparative Synthesis Example 2)
[0161] A 50 mL four-necked flask equipped with a stirrer was placed in a nitrogen atmosphere, 0.518 g (2.60 mmol) of DA-3 and 2.51 g (10.3 mmol) of DA-4 were weighed, 42.3 g of NMP was added, and the mixture was dissolved by stirring while nitrogen was supplied. 2.71 g (12.4 mmol) of CA-2 was added while stirring the diamine solution, and the mixture was stirred at room temperature for 2 hours and then at 50° C. for 24 hours to obtain a polyamic acid solution (PAA-8, viscosity: 531.5 mPa·s).
[0162] (Comparative Synthesis Example 3)
[0163] A 50 mL four-necked flask equipped with a stirrer was placed in a nitrogen atmosphere, 1.04 g (5.21 mmol) of DA-3 and 1.91 g (7.82 mmol) of DA-4 were weighed, 41.4 g of NMP was added, and the mixture was dissolved by stirring while nitrogen was supplied. 2.71 g (12.4 mmol) of CA-2 was added while stirring the diamine solution, and the mixture was stirred at room temperature for 2 hours and then at 50° C. for 24 hours to obtain a polyamic acid solution (PAA-9, viscosity: 542.2 mPa·s).
[0164] (Comparative Synthesis Example 4)
[0165] A 50 mL four-necked flask equipped with a stirrer was placed in a nitrogen atmosphere, 0.51 g (2.56 mmol) of DA-3 and 2.97 g (10.4 mmol) of DA-5 were weighed, 47.2 g of NMP was added, and the mixture was dissolved by stirring while nitrogen was supplied. 2.71 g (12.4 mmol) of CA-2 was added while stirring the diamine solution, and the mixture was stirred at room temperature for 2 hours and then at 50° C. for 24 hours to obtain a polyamic acid solution (PAA-10, viscosity: 547.1 mPa·s).
[0166] (Comparative Synthesis Example 5)
[0167] A 50 mL four-necked flask equipped with a stirrer was placed in a nitrogen atmosphere, 0.51 g (2.56 mmol) of DA-3 and 2.97 g (10.4 mmol) of DA-5 were weighed, 47.2 g of NMP was added, and the mixture was dissolved by stirring while nitrogen was supplied. 2.71 g (12.4 mmol) of CA-2 was added while stirring the diamine solution, and the mixture was stirred at room temperature for 2 hours and then at 50° C. for 24 hours to obtain a polyamic acid solution (PAA-11, viscosity: 547.1 mPa·s).
[0168] (Comparative Synthesis Example 6)
[0169] A 50 mL (liter) four-necked flask equipped with a stirrer was placed in a nitrogen atmosphere, 3.29 g (11.0 mmol) of DA-1 was weighed, 46.1 g of NMP was added, and the mixture was dissolved by stirring while nitrogen was supplied. 1.91 g (9.7 mmol) of CA-1 was added while stirring the diamine solution, and the mixture was stirred at 15° C. for 2 hours to obtain a polyamic acid solution (PAA-12, viscosity: 121.1 mPa·s).
[0170] (Comparative Synthesis Example 7)
[0171] A 50 mL four-necked flask equipped with a stirrer was placed in a nitrogen atmosphere, 2.77 g (13.0 mmol) of DA-2 was weighed, 46.1 g of NMP was added, and the mixture was dissolved by stirring while nitrogen was supplied. While stirring the diamine solution, 2.34 g (11.9 mmol) of acid dianhydride (CA-1) was added, and the mixture was stirred at 15° C. for 2 hours to obtain a polyamic acid solution (PAA-13, viscosity: 110.4 mPa·s).
[0172] <Examples 1 to 6 and Comparative Examples 1 to 7>
[0173] 24.0 g of each of the 10-12% polyamic acid solutions PAA-1 to PAA13 obtained in the above-mentioned Synthesis Examples 1 to 6 and Comparative Synthesis Examples 1 to 7 were taken, and 5.6 g of NMP, 8.00 g of BCS and 2.4 g of a mixed solution containing 1 wt % of LS-4668 were added thereto while stirring, followed by stirring at room temperature for 2 hours to obtain liquid crystal aligning agents (AL-1) to (AL-13), respectively.
[0174] <Evaluation>
[0175] The above-described liquid crystal orientation and Gardner chromaticity were evaluated for each of the liquid crystal aligning agents (AL-1) to (AL-13) of Examples 1 to 6 and Comparative Examples 1 to 7 obtained above. The results are shown in Table 1. In Table 1, "-" indicates that the Gardner chromaticity was not measured.
[0176] [Table 1]
[0177]
[0178] Industrial Applicability
[0179] The liquid crystal aligning agent of the present invention is used in a wide range of fields such as large-scale liquid crystal display elements and mobile liquid crystal display elements such as smartphones and cell phones, which require high definition and low cost.
[0180] It should be noted that the entire contents of the specification, claims, drawings, and abstract of Japanese Patent Application No. 2016-168461 filed on August 30, 2016 are incorporated herein by reference in their entirety and are incorporated as a disclosure of the specification of the present invention.
Claims
1. A liquid crystal alignment agent, characterized in that: The invention contains at least one polymer selected from the group consisting of a polyamic acid and a polyimide obtained by imidizing the polyamic acid, wherein the polyamic acid is obtained by reacting a diamine component containing a diamine having a structure represented by the following formula [1] with a tetracarboxylic dianhydride component, In the formula, A represents a thermally releasable group which is replaced by a hydrogen atom by heating at a temperature of 150 to 300° C.; the hydrogen atom possessed by the benzene ring may be substituted by an alkyl or alkoxy group having 1 to 5 carbon atoms, or a halogen group; * represents a connecting bond; The diamine having a structure represented by formula [1] is a diamine represented by any of the following formulae, wherein Boc represents a tert-butoxycarbonyl group, The diamine component further comprises DA-4, DA-6, 1,2-bis(4-aminophenyl)ethane, 1,3-bis(4-aminophenyl)propane, 1,4-bis(4-aminophenyl)butane, 1,5-bis(4-aminophenyl)pentane, 1,6-bis(4-aminophenyl)hexane, 1,7-bis(4-aminophenyl)heptane, 1,8-bis(4-aminophenyl)octane, 1,9-bis(4-aminophenyl)nonane, 1,10-bis(4-aminophenyl) 1,4-bis(4-aminophenoxy)butane, 1,5-bis(4-aminophenoxy)pentane, 1,6-bis(4-aminophenoxy)hexane, 1,8-bis(4-aminophenoxy)octane, 1,9-bis(4-aminophenoxy)nonane, 1,10-bis(4-aminophenoxy)decane, bis(4-aminophenyl) 1,3-malonate, bis(4-aminophenyl) 1,4- succinate, bis(4-aminophenyl) 1,5-pentanedioate, bis(4-aminophenyl) 1,6-adipate, bis(4-aminophenyl) 1,7-pimelate, bis(4-aminophenyl) 1,8-subanedioate, bis(4-aminophenyl) 1,9-azelaate, bis(4-aminophenyl) 1,10-sebacate, 1,3-bis[4-(4-aminophenoxy)phenoxy]propane, 1,4-bis[4-(4-aminophenoxy)phenoxy]butane at least one diamine selected from the group consisting of 1,5-bis[4-(4-aminophenoxy)phenoxy]pentane, 1,6-bis[4-(4-aminophenoxy)phenoxy]hexane, 1,7-bis[4-(4-aminophenoxy)phenoxy]heptane, 1,8-bis[4-(4-aminophenoxy)phenoxy]octane, 1,9-bis[4-(4-aminophenoxy)phenoxy]nonane, and 1,10-bis[4-(4-aminophenoxy)phenoxy]decane, 2. The liquid crystal alignment agent according to claim 1, wherein The content of the diamine having a structure represented by formula [1] in the diamine component is 5 to 95 mol%.
3. The liquid crystal aligning agent according to claim 1 or 2, wherein: The tetracarboxylic dianhydride component is a compound represented by the following formula [7]: In the formula, Z1 is a tetravalent organic group having 4 to 13 carbon atoms and has an aromatic cyclic hydrocarbon group.
4. The liquid crystal alignment agent according to claim 3, wherein: Z1 is any one of the structures represented by any one of the following formulas [7a] to [7k], 5 . A liquid crystal alignment film obtained from the liquid crystal alignment agent according to claim 1 . 6 . A liquid crystal display element comprising the liquid crystal aligning film according to claim 5 .
Citation Information
Patent Citations
Formation of oriented film
JP1990223916A
Liquid crystal orienting agent
JP1992281427A
New liquid crystal orienting agent
JP1993043687A
Polymer as orientation layer
JP1994287453A
Method for orienting liquid crystal
JP1997297313A